Chemometrics for analytical chemistry - Meloun, M. (Milan), 1943-; Militky, Jiri; Forina, Michele (New York : Ellis Horwood, 1992)
Vol.1. PC-aided statistical data analysis -- vol.2. PC-aided regression and related methods